The importance of values and leadership in shaping the pro-social behavior of future sports organization leaders - Vladimirova T.N. ,; Tamarskaya N.V. ,; Seryakova S.B. ,; Novikova I.S. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determining the nature, extent, and hierarchy of leadership abilities and life priorities of future leaders in sports-oriented organizations is a crucial aspect in fostering their pro-social engagement. Methods and structure of the study. The research was carried out at the Institute of Physical Culture, Sports, and Health at Moscow State University, focusing on graduate students. The methods employed included the «Morphological Test of Life Values» (V.F. Sopov, 2001), the «Diagnosis of Leadership Abilities» (R.V. Nemov, 2001), the «Self-Assessment of Leadership Style» (T.V. Bendas, 2006), and the methodology for the study of prosocial behavior (D.V. Sochivko, 2019). Results and conclusions. It was discovered that the more pronounced the leadership traits among students at the Institute of Physical Culture, Sports, and Health, the more likely they are to exhibit empathy and altruism as forms of pro-social behavior. Conversely, the less they value material security, the more likely they are to display narcissism and social anxiety as forms of pro-social behavior. Additionally, the higher the students' self-perception of their leadership abilities in a business context, the more likely they are to engage in manipulative behavior as a form of social interaction.